2020
DOI: 10.1097/phm.0000000000001473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time to Receipt of Prosthesis on Total Healthcare Costs 12 Months Postamputation

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Early ambulation can be advantageous as it helps to minimize joint contractures and deconditioning, and is associated with higher levels of prosthesis use. 32 , 33 A recent study by Miller et al found that receiving a prosthesis earlier, within the first 3 months’ post-amputation, reduced health care costs by $25,000 during the following year. 32 Past studies have found that only 26% 34 to 57% 35 of people with a transfemoral amputation receive a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early ambulation can be advantageous as it helps to minimize joint contractures and deconditioning, and is associated with higher levels of prosthesis use. 32 , 33 A recent study by Miller et al found that receiving a prosthesis earlier, within the first 3 months’ post-amputation, reduced health care costs by $25,000 during the following year. 32 Past studies have found that only 26% 34 to 57% 35 of people with a transfemoral amputation receive a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 A recent study by Miller et al found that receiving a prosthesis earlier, within the first 3 months’ post-amputation, reduced health care costs by $25,000 during the following year. 32 Past studies have found that only 26% 34 to 57% 35 of people with a transfemoral amputation receive a prosthesis. A study in the U.S. Department of Veterans Affairs found that patients who received a prosthesis within a year from amputation had a 25% 3-year mortality rate versus 45% for those who did not receive a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…23 It should be noted that the cost of prosthetic provision has been shown to be less than 10% of the total cost of an amputation, 45 with delayed rehabilitation adding considerable expense to the total cost. 2 It has also been demonstrated that less time between amputation and weight bearing or ambulation therapy can both contribute to faster restoration of the walking ability after a lower limb amputation 46 and reduce the cost of rehabilitation of these patients. 2 Using DS-TF a prosthetist can potentially reduce the time between amputation and start of weight bearing and physical therapy down to 6 weeks as shown in study when using the DS-TT.…”
Section: Cpojmentioning
confidence: 99%
“…It is understood that the sooner a patient can begin gait training with their definitive socket, the better. 21,22 The Direct Socket TF (DS-TF) enables a prosthetist to fabricate a custom-made interface directly on the residual limb in a single visit, similar to Direct Socket TT. 23 The proximal portion of a DS-TF interface design differs from the proximal portion of sockets, typically included in the above described IRC sockets designs, 16 as the proximal part of the DS-TF incorporates a size-specific silicone brim instead.…”
Section: Introductionmentioning
confidence: 99%